Measurement of the Zakat Transparency Index of Amil Zakat Institutions (LAZ) in Banten Province, Indonesia - Ahmad Fatoni; Muhamad Fakhrudin (Institut Agama Islam Negeri Kendari, 2021)
As an institution that manages social funds, transparency must be met for the Amil Zakat Institution. By measuring the zakat transparency index, the Amil Zakat Institution can find out the extent of the implementation of transparency in the organisation. Information disclosure to the public is believed to increase public confidence in paying zakat at the Amil Zakat Institution. This study aims to measure the zakat transparency index of the Amil Zakat Institution in Banten Province. The Simple Additive Weighting (SAW) method is used to calculate the transparency index of zakat institutions. The Simple Additive Weighting (SAW) method is a multiple attribute retrieval method, where the weight of each predetermined dimension is multiplied by each variable weight, then added up. The results showed that the Amil Zakat Institution in Banten Province was included in the reasonably transparent category with an index of 0.706.